Proceedings of the International Conference on Research and Academic Community Services (ICRACOS 2019) 2020
DOI: 10.2991/icracos-19.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Learning Need Assessment: Formulating Blended-Learning as Academic Services for Student-Athletes

Abstract: There is no other way to succeed in many ways except to do more business. That is what happens to studentathletes who study at Physical Education Teacher Education (PETE). They must perform optimally as athletes, as well as success in learning to achieve maximum academic achievement. For this reason, instructors must provide learning services that enable students to continue to conduct a series of training centers without having to leave the academic learning process. In order for learning service formulas to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…Untuk memulai perkuliahan perlu diadakan need-assessment berhubungan dengan tujuan utama perkuliahan. Need-assessment diperlukan untuk mengetahui kebutuhan belajar mahasiswa agar proses perkuliahan dapat lebih bermakna dan berdampak sesuai dengan kebutuhan mahasiswa (Priambodo et al, 2020)…”
Section: Pendahuluanunclassified
“…Untuk memulai perkuliahan perlu diadakan need-assessment berhubungan dengan tujuan utama perkuliahan. Need-assessment diperlukan untuk mengetahui kebutuhan belajar mahasiswa agar proses perkuliahan dapat lebih bermakna dan berdampak sesuai dengan kebutuhan mahasiswa (Priambodo et al, 2020)…”
Section: Pendahuluanunclassified
“…So with such a learning model in a short time, the quality of learning is less than optimal. Priambodho et al [4] revealed that the students needed lectures that were conducted by combining distance and face-to-face learning. One solution is to provide a learning management system (LMS) as an online class for distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over half (51.6%) the students stop sports without any external extenuating circumstances [9]. Student-athletes may have more difficulty in adjusting because of several intrinsic characteristics that should be considered when developing assistance programs [10]. As the curriculum in Korea consists of 6 years of elementary school, 3 years of junior high school, and 3 years of high school, it is necessary to adapt to the new environment whenever the class changes.…”
Section: Introductionmentioning
confidence: 99%